Oxygen Regulates Human Pluripotent Stem Cell Metabolic Flux - Jarmon G. Lees; Timothy S. Cliff; Amanda Gammilonghi; James G. Ryall; Stephen Dalton; David K. Gardner; Alexandra J. Harvey (Stem Cells International)
Metabolism has been shown to alter cell fate in human pluripotent stem cells (hPSC). However, current understanding is almost exclusively based on work performed at 20% oxygen (air), with very few studies reporting on hPSC at physiological oxygen (5%). In this study, we integrated metabolic, transcriptomic, and epigenetic data to elucidate the impact of oxygen on hPSC. Using 13C-glucose labeling, we show that 5% oxygen increased the intracellular levels of glycolytic intermediates, glycogen, and the antioxidant response in hPSC. In contrast, 20% oxygen increased metabolite flux through the TCA cycle, activity of mitochondria, and ATP production. Acetylation of H3K9 and H3K27 was elevated at 5% oxygen while H3K27 trimethylation was decreased, conforming to a more open chromatin structure. RNA-seq analysis of 5% oxygen hPSC also indicated increases in glycolysis, lysine demethylases, and glucose-derived carbon metabolism, while increased methyltransferase and cell cycle activity was indicated at 20% oxygen. Our findings show that oxygen drives metabolite flux and specifies carbon fate in hPSC and, although the mechanism remains to be elucidated, oxygen was shown to alter methyltransferase and demethylase activity and the global epigenetic landscape.